ESTUDIO DE SALUD Y ENVEJECIMIENTO EN CIUDAD VICTORIA (ESEV) -MÉXICO-: METODOLOGÍA Y DATOS PRINCIPALES - Rivera Navarro, Jesús; Benito-León, Julián; Pazzi Olazaran, Karla Amalia; Mancinas Espinoza, Sandra Elizabeth (RESPYN Revista Salud Pública y Nutrición, 2009)
Evaluar la salud del adulto mayor en Ciudad Victoria –Estado de Tamaulipas- México, mediante variables y escalas basadas en la auto-evaluación. Las fuentes de muestreo para la selección de la población diana fueron el Registro Federal de los electores y el Instituto Nacional de Estadística, Geografía e Informática. En la entrevista se usaron escalas para medir la red social, la depresión, el estado cognoscitivo, y las actividades de la vida diaria. 1231 personas de 60 años y más fueron entrevistados. El 57.9% eran mujeres, la edad media fue de 70.03, y el 27.1 trabajaba de manera remunerada. La enfermedad más prevalente era la hipertensión. Más del 80% consideraba tener un buen apoyo social, y el 29% tenía sintomatología depresiva. El estudio ESEV captó múltiples facetas, directas e indirectas, de la salud de los adultos mayores. Se deben emprender estudios similares pero de tipo longitudinal. Abstract. To analyze older adults’ health in Ciudad Victoria – Tamaulipas state-Mexico, through items and scales related to health auto-evaluation. The sources of sampling for the selection of potential enrollees were Federal Register of Electors and National Institute of Statistic, Geography and Computing (INEGI). From first source we got first and last names, ages, genders and addresses of all individuals more than 60 years who lived in Ciudad Victoria in that moment. From INEGI we got: the territorial division of the city by block units called AGEBS -one AGEB include from 25 to 50 blocks- and, 2) every individual, by age and gender, who lived in every AGEB. In the applied questionnaire were used scales for measuring social support, depression, cognitive state, and daily life activities. 1231 persons of 60 years and more were interviewed. 57% were women, average age was 70.03, and 27.1 worked. Disease more prevalent was hypertension. More than 80% said to have a good social support and 29% had depressive symptomatology. ESEV study captured several aspects, direct and indirect, of older adults’ health. It must be undertaken similar studies although longitudinal in spite of cross-sectional surveys. Palabras clave: Envejecimiento, epidemiología, depresión, deterioro cognitivo, dependencia.